Modeling of Atmospheric Gravity Effects for High-Precision Observations - Gitlein, Olga; Timmen, Ludger; Müller, Jürgen (Delaware : Scientific Research Publishing Inc., 2013)
Temporal variations of atmospheric density distribution induce changes in the gravitational air mass attraction at a specific observation site. Additionally, the load of the atmospheric masses deforms the Earth’s crust and the sea surface. Variations in the local gravity acceleration and atmospheric pressure are known to be corrected with an admittance of about 3 nm/s2 per hPa as a standard factor, which is in accordance with the IAG Resolution No. 9, 1983. A more accurate admittance factor for a gravity station is varying with time and depends on the total global mass distribution within the atmosphere. The Institut für Erdmessung (IfE) performed absolute gravity observations in the Fennoscandian land uplift area nearly every year from 2003 to 2008. The objective is to ensure a reduction with 3 nm/s2 accuracy. Therefore, atmospheric gravity changes are modeled using globally distributed ECMWF data. The attraction effect from the local zone around the gravity station is calculated with ECMWF 3D weather data describing different pressure levels up to a height of 50 km. To model the regional and global attraction, and all deformation components the Green’s functions method and surface ECMWF 2D weather data are used. For the annually performed absolute gravimetry determinations, this approach improved the reductions by 8 nm/s2 (-19 nm/s2 to +4 nm/s2). The gravity modeling was verified using superconducting gravimeter data at station Membach inBelgiumimproving the residuals by about 15%.